(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
India is the home to many tribal groups and ranks seventh among the world’s biodiversityhotspots. Aboriginal people developed a vast body of knowledge about the plants and their applicationsthrough comprehending the surrounding environment to satisfy their requirements. Recent research onconventional medicine has made it possible to identify other plants that produce drugs. Therefore, it iscrucial to gather data, provide documentation, and conduct research on ethnomedicine. The aim of is tostudy the antibacterial properties of selected plants used traditionally by the rurals of Banda district.